Reactive spark plasma sintering of exothermic systems: A critical review. Issue 3 (1st February 2022) - Mukasyan, A.S.; Rogachev, A.S.; Moskovskikh, D.O.; Yermekova, Zh.S.
Abstract: Spark plasma sintering (SPS) is an efficient method for fabricating various bulk dense materials, including ceramics. Reactive spark plasma sintering (RSPS) of the exothermic reaction systems involves an initial powder mixture that allows chemical transformation with release of an additional energy during the SPS process. Thus, a deep understanding of the chemistry is critical for controlling the microstructure and thus the properties of the obtained materials. Recent publications have revealed that the RSPS is widely used for manufacturing of variety of materials including ultrahigh-temperature ceramics, high-entropy ceramics, and thermoelectrics. However, the thermodynamics and kinetics of the chemical reactions occurring during RSPS are not well understood. The goals of the present critical review are as follows: (i) to provide the fundamental definitions of chemistry related parameters of RSPS; (ii) to analyze the thermodynamics and kinetics of the RSPS processes; (iii) to emphases the influence of the microstructure of the consolidated media on the chemistry of RSPS; (iv) briefly overview recent publications on RSPS of ceramics. We also provide some recommendations for future work in the field of RSPS.